A PRELIMINARY STUDY OF PHYSICS LEARNING THROUGH THE INTEGRATION OF MULTIVERSE NARRATIVE AND HYPOTHETICAL PHYSICS MODELING IN ENHANCING STUDENTS' SCIENTIFIC IMAGINATION - Pathurrahman; Rudi Purwanto (INERCYS: Institute of Educational, Research, and Community Service, 2025)
Physics learning through the integration of multiverse narrative and hypothetical physics modeling constitutes an important aspect of physics education because conventional instructional approaches often limit students’ scientific imagination and their ability to explore abstract, speculative, and frontier concepts in modern physics. This limitation highlights the need for further research focusing on instructional strategies that explicitly promote imaginative reasoning while preserving scientific rigor. This preliminary study aims to examine the effectiveness of integrating multiverse narratives with hypothetical physics modeling in enhancing students’ scientific imagination and learning engagement in physics. The study employed an experimental method with a quasi-experimental design involving an experimental group and a control group. Data were collected using scientific imagination assessment tests, learning engagement observation sheets, and instructional documentation, and were analyzed through descriptive statistics and inferential analysis using an independent samples t-test. The results reveal that students in the experimental group demonstrated significantly higher scientific imagination scores (M = 84.2; SD = 6.5) compared to the control group (M = 71.6; SD = 7.3), with a statistically significant difference (t(58) = 5.72, p < 0.001) and a strong effect size (Cohen’s d = 0.88). In addition, learning engagement in the experimental group was categorized as high (M = 4.21) relative to the control group (M = 3.36), indicating more active participation in exploratory discussion, conceptual speculation, and reflective reasoning. These findings illustrate that the integration of multiverse narratives with hypothetical physics modeling effectively fosters scientific imagination and cognitive engagement by providing a structured space for speculative yet theory-informed thinking. This study contributes significantly to the advancement of physics education at both national and international levels by proposing an innovative pedagogical framework that bridges narrative-based learning, theoretical modeling, and imaginative science education. Furthermore, the findings are expected to serve as a reference for future research on creative physics instruction, speculative science learning, and interdisciplinary approaches that support the development of higher-order thinking skills in 21st-century physics education.